Semana Santa Tradition Educational Symbol - Wissang, Imelda Oliva, Dawud, Sumadi; Pratiwi, Yuni (CENTRAL ASIA AND THE CAUCASUS, 2022)
This article aims to explain the educational symbols of the Semana Santa tradition, a religious tradition that exists in Larantuka, East Flores, East Nusa Tenggara. This research is qualitative research using an autoethnographic type of research that emphasizes the experience and reflexivity of the researcher as a source of data supported by data from sources and field notes. Collecting data using observation and interview techniques. Data analysis used autoethnographic techniques with ethnographic-interactive analysis stages. The theory used is ethnosemiotic theory to find the meaning of culture as a peculiarity contained in the symbols of the Semana Santa tradition. The Semana Santa tradition is a cultural specialty of the Lamaholot community with educational symbols that describe the life of the Lamaholot community. The educational symbols of the Semana Santa tradition are (1) korke bale,(2) trewa , (3) berobok , (4) denga deo, (5) persian Tuan Ma , and (6) serah punto dama. These six educational symbols as an upbringing express the beliefs, thoughts, and attitudes of the Lamaholot community, namely (1) maintaining religiosity as a legacy that strengthens faith, (2) maintaining unity as a legacy that strengthens brotherhood, (3) maintaining purification, self-purity as a strengthening legacy. harmony of life, (4) maintaining the uniqueness, distinctiveness of cultural traditions that strengthen identity, characteristics, identity, and (5) preserving nature as a heritage that maintains the balance of spiritual, spiritual, and physical, physical life.